An integrated approach to assessing the bio-activity of nutrients in vitro: The anti-oxidant effects of catechin and chlorogenic acid as an example. Issue 4 (2015) - McCann, Mark J.; Dalziel, Julie E.; Bibiloni, Rodrigo; Barnett, Matthew P.G.
No abstract available